2018
DOI: 10.1039/c8ra07236a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient conversion of CO2 to cyclic carbonates with a binary catalyst system in a microreactor: intensification of “electrophile–nucleophile” synergistic effect

Abstract: An intensification of the “electrophile–nucleophile” synergistic effect was achieved in a microreactor for the coupling reaction of CO2 and epoxides mediated by the binary Al complex/ternary ammonium salt catalyst system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, the intensification of mass transfer has not received significant attention . The most commonly reported strategy for intensifying gas–liquid mixture mass transfer is the utilization of a microreactor. Chen et al reported that improved efficiency, compared to that of a stirred tank reactor (STR) with respect to the production of PC, can be attained using a microreactor . Similarly, we have achieved synergistic catalysis of cycloaddition reactions via a microreactor to produce various cyclic carbonates in an efficient manner .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the intensification of mass transfer has not received significant attention . The most commonly reported strategy for intensifying gas–liquid mixture mass transfer is the utilization of a microreactor. Chen et al reported that improved efficiency, compared to that of a stirred tank reactor (STR) with respect to the production of PC, can be attained using a microreactor . Similarly, we have achieved synergistic catalysis of cycloaddition reactions via a microreactor to produce various cyclic carbonates in an efficient manner .…”
Section: Introductionmentioning
confidence: 83%
“…30 Similarly, we have achieved synergistic catalysis of cycloaddition reactions via a microreactor to produce various cyclic carbonates in an efficient manner. 31 These results revealed that the structures of the reactor significantly influence the mass transfer of the gas−liquid reaction, thus affecting the production efficiency. The jet loop reactor (JLR), a loop reactor equipped with a self-priming ejector, is capable of improving the specific surface area of the gas−liquid contact according to the Venturi principle.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the alleged inert nature of CO 2 leads to extended reaction times, hampering the global process efficiency. [26][27][28][29] Various carbonation protocols using CO 2 on oxiranes with homogeneous and heterogeneous catalysts have been reported under flow conditions, [30][31][32][33] among which only two reports specifically disclosed the carbonation of 2 (Figure 1b,c) [22,25] with low overall productivities.…”
Section: Ambitious Randd and Production Directives In Europe Nowmentioning
confidence: 99%
“…The catalytic synthesis of cyclic carbonate from epoxides and CO 2 is considered to be one of the most promising pathways to CO 2 utilization. [12][13][14] Cyclic carbonates have wide applications as green polar aprotic solvents, fuel additives, and chemical intermediates. [15][16][17][18] The chemical xations of CO 2 into cyclic carbonates are relatively simple from a chemical reactivity point of view, while in fact, the high temperature, high pressure, high catalyst loading, or a combination of these are required to make the reaction effective, which is not economically suitable and poses safety concerns as well.…”
Section: Introductionmentioning
confidence: 99%